Metacognition and second/foreign language learning - Raoofi, Saeid; Chan, Swee Heng; Mukundan, Jayakaran; Md Rashid, Sabariah (Canadian Center of Science and Education, 2014)
Metacognition appears to be a significant contributor to success in second language (SL) and foreign language (FL) learning. This study seeks to investigate empirical research on the role metacognition plays in language learning by focusing on the following research questions: first, to what extent does metacognition affect SL/FL learning? Second, what are the factors shown to influence metacognition of learners in the area of second/foreign language learning? Data from 33 studies published between 1999 and 2013 were coded based on a coding scheme adapted from previous systematic reviews (e.g., Norris & Ortega, 2001; Plonsky, 2011). The findings of the review show that the metacognitive interventions have the possibility to promote language performance, but, on the whole, mixed evidence was found for the effectiveness of the intervention in enhancing metacognitive awareness/strategy use. The results also indicate that several factors appeared to affect L2 learners’ metacognition. This review expands our understanding of the role of metacognition in language learning and will lead to pedagogical implications for SL/FL learning and teaching. Limitations of the existing studies and directions for future research are also discussed.